Tensile Testing of Polymers: Integration of Digital Image Correlation, Infrared Thermography and Finite Element Modelling - Song, P; Trivedi, A; Siviour, C (University of Oxford, 2022)
These data are the raw and processed data to support the paper: "Tensile testing of polymers: Integration of digital image correlation, infrared thermography and finite element modelling".